Perfluorooctyl bromide & indocyanine green co-loaded nanoliposomes for enhanced multimodal imaging-guided phototherapy. (May 2018) - Sheng, Danli; Liu, Tianzhi; Deng, Liming; Zhang, Liang; Li, Xuelin; Xu, Jie; Hao, Lan; Li, Pan; Ran, Haitao; Chen, Hangrong; Wang, Zhigang
Abstract: As a highly biocompatible NIR dye, indocyanine green (ICG) has been widely explored for cancer treatment due to its various energy level transition pathways upon NIR light excitation simultaneously, which leads to different theranostic effects ( eg. Photoacoustic (PA) and fluorescence imaging (FL), photodynamic and photothermal therapy (PDT&PTT)). However, the theranostic efficiency of ICG is restricted intrinsically, owing to the competitive relationship of its co-existing imaging and therapeutic effect. Moreover, the extrinsic hypoxia nature of tumor further limits its therapeutic effect, especially for the oxygen-dependent PDT. Herein, perfluorooctyl bromide (PFOB), another biocompatible chemical, was integrated with ICG in a nanoliposome structure via a facile two-step emulsion method. Such an ICG&PFOB co-loaded nanoliposomes (LIP-PFOB-ICG) realized computed tomography (CT) contrast imaging in vivo, providing better anatomical information of tumor in comparison to ICG enabled PA and FL imaging. More importantly, LIP-PFOB-ICG inhibited MDA-MB-231 tumor growth completely via intravenous injection through enhanced PDT&PTT synergistic therapy due to the excellent oxygen carrying ability of PFOB, which effectively attenuated tumor hypoxia, improved the efficiency of collisional energy transfer between ICG and oxygen and reduced the expression of heat shock protein (HSP). As expected, the introduction of PFOB within nanoliposomes with ICG has augmented the theranostic effect of ICG comprehensively, which makes this simple biocompatible liposome-based nanoagent a potential candidate for clinical imaging guided phototherapy of cancer. Graphical abstract: